Aesthetic evaluation after non‐invasive treatment for superficial basal cell carcinoma. (21st November 2011) - Mosterd, K.; Arits, A.H.M.M.; Nelemans, P.J.; Kelleners‐Smeets, N.W.J.
Abstract Background Cosmetic results following non‐invasive treatments are difficult to compare. Although qualified objective scar assessment scales are available, they are not used in dermatological studies. Usually a 4‐point scale is used in dermatological scars. The reproducibility of this method has never been evaluated. Moreover, significant specific scar characteristics are lacking. The patient and observer scar assessment scale (POSAS) is a scale qualified for the assessments of surgical scars. It has proven to be as reliable as the widely used Vancouver Scar Scale, but has the advantage that it includes the patient's opinion and specifies different scar characteristics. Objective Both methods were used to evaluate cosmetic results following non‐invasive treatments of superficial basal cell carcinoma (BCC). Methods A total of 54 lesions following non‐invasive treatment for BCC in 54 patients were evaluated with the traditional 4‐point scale and the POSAS. Results The 4‐point scale showed the best reproducibility and had an intra‐class correlation coefficient (ICC) of 0.66 (95% CI: 0.52–0.77) for a single observer and 0.85 (95% CI: 0.77–0.91) for multiple observers. The ICC of the POSAS was 0.41 (95% CI: 0.21–0.58) for a single observer and 0.67 (95% CI: 0.45–0.81) for three observers. The scar characteristics, vascularity and pigmentation were most decisive for the overall opinion. Conclusion The use of the 4‐point scale is a valid method to compare scars of non‐invasive dermatological treatments. Supplementary registering vascularity and pigmentation can be useful in future studies.